Reay, Popular Cultures In England 1550-1750; Marsden Ed., Victorian Values - Personalities And Perspectives In Nineteenth-Century Society - McAllister, Charlie (Teaching History: A Journal of Methods, 2000)
If you can tell a book by its cover, then the covers of these two books reveal the differences in their eras and their approaches. Barry Reay’s Popular Cultures features a detail from William Hogarth’s March of the Guards to Finchley (1750) which captures a typically busy Hogarthian moment of boisterous pursuits. Local girls flirt with soldiers, a curious couple smoke pipes, and two prize-fighters square off in a lively crowd.